Live like nobody is watching : relational autonomy in the age of artificial intelligence health monitoring - Ho, Anita (Bioethicist) (New York, NY : Oxford University Press, 2023)
As our society embraces expanding forms of personal and health monitoring, particularly with the use of artificial intelligence (AI), how may these technologies change the way we define what it means to live a free and healthy life? Drawing on the examples of home health monitoring, direct-to-consumer health apps, and medication adherence monitoring, this book explores the socio-relational contexts that are framing the promotion of AI health monitoring, and the potential consequences of the proliferation of these technologies. It argues for a relational conception of autonomy and explores how socio-systemic conditions shape the cultural meanings of personal responsibility, healthy living and aging, trust, and caregiving in the era of big data and AI. This book proposes ethical strategies that can help preserve and promote people's relational autonomy in the digital era.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 5, 2023).
Keywords: Patient monitoring -- Technological innovations -- Moral and ethical aspects; Artificial intelligence -- Medical applications -- Moral and ethical aspects; Society; Ethics & moral philosophy